PENGARUH KEPEMIMPINAN, KOMPENSASI DAN KOMITMEN ORGANISASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN MARKETING PT. ASURANSI BUMI PUTRA - Nengsih, Verly Septia; Indarti, Sri; Rifqi, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
Low labor productivity was a problem that was often faced by a company in its efforts to increase the benefits to be achieved. The purpose of this study was to look at the effect of leadership, compensation and organizational commitment to employee productivity marketing at PT. Asuransi Bumi Putra. The population in this study amounted to 59 people. While the sampling technique is done by census method. Data analysis using multiple linear regression with SPSS 18.0. Based on the survey results revealed that the leadership, compensation and organizational commitment simultaneous and partial effect on employee productivity PT. Asuransi Bumi Putra.Keywords : Leadership, Compensatio